Housing improvement in a marginal settlement the case of the UNEP/NHA Barrio Escopa project - Ocampo, Romeo B. (Philippine Journal of Public Administration, 1981)
Site and dwelling improvements were undertaken in 1978-1979 as part of a multi-component, "integrated," and innovative effort at slum rehabilitation in Quezon City, the Philippines. The housing and environmental systems (HES) activities included the reblocking and upgrading of sections of the existing community and the construction of shell houses for relocatees at a New Site nearby. The subproject was able to improve housing conditions for the residents involved, afforded active local participation, and generated some employment and income in the process. But like the larger project, HES did so only after much difficulty and delay due to the innovations attempted and to intervening external events.